2022
DOI: 10.1371/journal.pone.0270111
|View full text |Cite
|
Sign up to set email alerts
|

Imaging-based indices combining disease severity and time from disease onset to predict COVID-19 mortality: A cohort study

Abstract: Background COVID-19 prognostic factors include age, sex, comorbidities, laboratory and imaging findings, and time from symptom onset to seeking care. Purpose The study aim was to evaluate indices combining disease severity measures and time from disease onset to predict mortality of COVID-19 patients admitted to the emergency department (ED). Materials and methods All consecutive COVID-19 patients who underwent both computed tomography (CT) and chest X-ray (CXR) at ED presentation between 27/02/2020 and 13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…The main limitation of our study is its retrospective nature. The RALE score is subject to interobserver variability, although the degree of agreement between RALE score points and lung involvement on CTPA is high [47]. Finally, the model was constructed with COVID-19 patients and suspected PT who underwent a CTPA to obtain a certain diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…The main limitation of our study is its retrospective nature. The RALE score is subject to interobserver variability, although the degree of agreement between RALE score points and lung involvement on CTPA is high [47]. Finally, the model was constructed with COVID-19 patients and suspected PT who underwent a CTPA to obtain a certain diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…The RALE assessment has been found to be associated with a worse outcome in different conditions, such as ARDS [ 28 , 31 ], refractory cardiogenic shock and refractory cardiac arrest [ 32 ]. Interestingly, in recent studies the RALE score has been indicated among the variables associated with a higher risk of death in COVID-19 patients [ 29 , 30 , 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, as published previously [42,43] The main limitation of our study is its retrospective nature. The RALE score is subject to interobserver variability, although the degree of agreement between RALE score points and lung involvement on CTPA is high [44].Finally, the model was constructed with COVID-19 patients and suspected PE who underwent a CTPA to obtain a certain diagnosis. Therefore, the model is applicable in this clinical scenario.…”
Section: Discussionmentioning
confidence: 99%